A new arthropod from the Silurian Konservat-Lagerstatte of Herefordshire, UK. - Orr, P; Siveter, D; Briggs, D; Siveter, D; Sutton, MD (2000)
A small, non-biomineralized, macrophagous arthropod with chelicerate affinities, Offacolus kingi gen. et sp. nov., from the Silurian (Wenlock Series) of Herefordshire, UK, is described. The dorsal exoskeleton comprises an arch-like cephalic shield, a thorax of three free tergites and a triangular posterior tagma of five fused tergites, the last with a stout postero-dorsally directed medial spine. Seven pairs of appendages beneath the cephalic shield surround a postero-medially sited oral cavity on the ventral surface of the head. Appendages I and, probably II are uniramous and project antero-ventrally; I was sensory and II sensory and/or ambulatory. Appendages III-VI are biramous, each with an antero-ventrally projecting ramus and a robust, highly geniculate, horizontally oriented ramus that projects through an anterior gape. The former rami were ambulatory and the latter have spinose terminal podomeres and functioned as a unit for trapping food and transferring it towards the oral cavity. Appendage VII, which is probably uniramous, is posteroventrally directed and flap like. Each tergite of the thorax and posterior tagma covers at least a pair (probably two pairs) of probably biramous appendages with each ramus flap like and setose.